Need for orthodontic treatment and its relationship with academic performance, self-esteem and bullying: a review of the literature - Machiavello, Edwin A. (2023)
The purpose of the present study was to conduct a literature review on the self-perception of the need for orthodontic treatment related to academic performance, self-esteem, and bullying. An electronic search was conducted for original articles (cross-sectional studies), meeting the inclusion and exclusion criteria, produced from 2018 to 2022, from the following databases: PubMed, Web of Science, Scopus, SciELO, and ScienceDirect, in English, Spanish, and Portuguese languages. Finally, 20 articles were selected that met the exclusion criteria and the study design.